TRANSPORTASI PUBLIK DAN MEDIA SOSIAL: PERSEPSI NETIZEN TERHADAP PELAYANAN BUS TRANS JOGJA 2016-2018 - Karmila Zahrani Al Hayati; Ridho Al-Hamdi (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
In the modern age, public transportation is needed by society, particularly in big cities. Thus, research of the netizens’ perception of the service quality of public transportation is fascinating to be examined further to know its recent development. The paper aims to measure the netizens’ perception of the service of Trans Jogja Bus between 2016 and 2018. Methodologically, this article is qualitative research with case study approach. Trans Jogja Bus is the case which will be the research focus. For data gathering, this research utilizes library research so that the data is coming from social media and online media news. There are nine indicators used as the analysis tool: tariff, route, time, safety, facility, service, necessary, dependability, and pollution. This research also utilizes online application word clouds and Netvizz to sharpen the analysis process. The finding demonstrates that most netizens have negative perceptions of the service of Trans Jogja Bus. It can be proven that most netizens deliver their negative perceptions in six indicators: route, time, safety, service, dependability, and pollution. In the meantime, merely three indicators which receive positive perceptions: tariff, facility, and necessity.